Early versus Late Brain Magnetic Resonance Imaging and Spectroscopy in Infants with Neonatal Encephalopathy following Therapeutic Hypothermia - Nuzum, Tatiana A.; Mally, Pradeep; Wachtel, Elena V. (American Journal of Perinatology, 2025)
This study aimed to evaluate the utility of early and late magnetic resonance imaging (MRI) in infants with neonatal encephalopathy (NE) after therapeutic hypothermia (TH), and to determine the concordance between magnetic resonance spectroscopy (MRS) and early MRI findings.We conducted a retrospective, observational study including encephalopathic neonates born between 2017 and 2023 at two regional perinatal centers. All subjects underwent early diffusion-weighted MRI (DWI) with or without MRS (day: 4–5), and late conventional T1/T2-weighted MRI (day: 12–14). Both MRIs were assigned an injury severity score based on the National Institute of Child Health and Human Development (NICHD) neonatal research network (NRN) pattern of injury, reflecting the injury apparent on the MR modality obtained. MRS injury was defined as the presence of a lactate peak.The majority of the cohort (n = 98) was moderately encephalopathic (78%). Early and late MR imaging was performed at an average of 5.7 and 13.6 days, respectively. Fifteen percent of infants had evidence of hypoxic-ischemic (HI) injury on early imaging only, and 6% on late imaging only. Forty percent of infants exhibited a change in NICHD score severity between early and late MRI. Twenty-three infants (24%) were found to have a milder injury and 16 (16%) were found to have more severe injury on late imaging, when scores were compared with early imaging scores. The concordance of injury between early MRS and MRI was 62.5%. Among the cases of discordant MRI/MRS, MRS detected additional injury in 70% of cases, and MRI detected additional injury in 30% of cases.Both early and late imaging are important to fully define injury and provide accurate neurodevelopmental prognoses in cases of encephalopathic infants following TH. Failure to perform imaging at two intervals would have potentially resulted in missed diagnoses in 6 to 15% of cases and misestimation of injury in up to 40% of cases.
Keywords: neonatal encephalopathy; magnetic resonance imaging; magnetic resonance spectroscopy; neuroimaging; neurodevelopmental prognostication